ORGANIZATIONAL CULTURE OF ISLAMIC PUBLIC EDUCATION MANAGEMENT A DISCURTIVE - Fauzi, Ahmad (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The presence of pesantren since XX century has significantly contributed to the development of institutional Islamic education. Even pesantren education is believed to be the oldest Islamic education in Indonesia, because the role of pesantren as educational institution (al-haiah al ta'lim wa al-tarbiyah), service and guidance of society (al-haiah al ta'awuny wa al takafuly wal al ittijaahi) and the struggle for society (al-haiah al-jihaadi li'izzi al-islaami wal muslimin). This view is sociologically, can give birth to the value system of local wisdom as a subculture of pesantren education. Therefore, the internalization of the aforementioned values becomes social capital for pesantren in moving the individual social behavior and into belief and core values to give birth to the effectiveness and productivity of work in Islamic education organizations and (noble industry). The social value system referred to, becomes a source of inspiration that is capable of inspiring all individual social actions, coordinating and controlling a group of people in a sorganization. Departing from the conceptual framework referred to, the basis of the foundation of the birth of Islamic education management organization culture by developing the values of local wisdom or tradition in boarding school.